MULTIPLE INTELLIGENCES AS A DIDACTIC STRATEGY TO PROMOTE INCLUSION IN BASIC GENERAL EDUCATION - Mayra Patricia Santana Moreira; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The Theory of Multiple Intelligences was developed by Howard Gardner in 1983, at present they have become strategies that have caused a high impact on education worldwide, these aim to discover the individual capacities of students and end the belief that a person is "intelligent" because of his ability to do mathematics or literature. They are based on the fact that each individual is different, and that learning is acquired by the combination of eight types of intelligences (linguistic, logical-mathematical, visualspatial, musical, kinetic-corporal, interpersonal, intrapersonal and naturalistic), which must be cultivated in the classroom through the development of skills and methods. To analyze the contributions of the theory of Multiple Intelligences and its strategies to attend to the diversity of students in an inclusive way, a bibliographic review on the foundations of these principles was needed through indexed journals, repositories and digital books, the method was applied inductive - deductive, the qualitative approach, allowing relationships between them and the contexts in which they unfold. The results determined that they could activate the multiple intelligences of the learners in the process, achieving significant learning, taking advantage of their most effective intelligence. Understanding that everyone is intelligent in a specific field, offer possibilities that allow teachers to lead their students to success, these opportunities also depend to a great extent on the environment in which they operate, culture, family, and society in general.